DYNAMIC NUMERICAL STRESS ANALYSIS OF A - Kacper CIEŚLAR; Jacek NOWAKOWSKI; Tomasz KNEFEL (Scientific Journal of Silesian University of Technology. Series Transport, 2025)
Dynamic numerical stress analysis of a crankshaft subjected to load at selected operational points of a diesel engine is presented in this paper. The calculations and the analyses were carried out for six values of engine rotational speed and for two temperature values of engine structural elements. At each operating point of the engine, the piston-crank system was loaded with maximal gas pressure force, and additionally, inertia forces resulting from rotational speed of the crankshaft were taken into consideration. The analysis was carried out to obtain the distribution of the stress and to indicate critical areas where concentration of the stress may occur. In addition, the analysis was extended to other operational factors, such as the determination of the natural frequency of vibrations and effects of maximal torque on torsion of the crankshaft.